2005
DOI: 10.1080/10428190500051380
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of patients with subcutaneous panniculitis-like T-cell lymphoma

Abstract: Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a rare form of cytotoxic T-cell lymphoma. The objective of this study was to characterize the clinical presentation, treatment, and prognosis of patients with SPTCL. Twenty-one patients with SPTCL were seen at Mayo Clinic (Rochester, Minnesota, USA) between July 1973 and June 2004. The median age at diagnosis was 42 years (range 23-80 years) and 15 (71%) were women. Constitutional symptoms occurred in 14 (67%) patients, including fever, serositis, arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 13 publications
0
48
1
1
Order By: Relevance
“…However, it was unclear whether this positive case was of the ab phenotype as their series included both ab and gd type cases, and the case described was published prior to the 2008 WHO classification. 10 In this study, we reported three cases of subcutaneous panniculitis-like T-cell lymphoma with focal bone marrow infiltration by lymphoma. None of the three bone marrow core biopsies exhibited large lymphocytic infiltrates.…”
Section: Discussionmentioning
confidence: 88%
“…However, it was unclear whether this positive case was of the ab phenotype as their series included both ab and gd type cases, and the case described was published prior to the 2008 WHO classification. 10 In this study, we reported three cases of subcutaneous panniculitis-like T-cell lymphoma with focal bone marrow infiltration by lymphoma. None of the three bone marrow core biopsies exhibited large lymphocytic infiltrates.…”
Section: Discussionmentioning
confidence: 88%
“…6,7 Reports in the literature describe remission with schedules such as CHOP and FMD. 2,3 However, our patient progressed in the third week after MEGACHOD and, although an initial response to FMD was observed, early progression occurred.…”
mentioning
confidence: 93%
“…1 Characteristically, delay and difficulty in making a diagnosis are common features of SPTCL. [2][3][4][5] Misdiagnosis is not uncommon owing to the indolent course of the disease, which can mimic an unspecific panniculitis. 6 In our report three biopsies and 6 months were required before the final diagnosis could be made, by which time the lymphoma had become aggressive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous lesions can occur with systemic symptoms such as fever, malaise, anorexia, and weight loss; they can also cause lipodystrophy after resolution. While extra-cutaneous involvement is uncommon, there have been reports of bone marrow, lymph node, liver, spleen, lung, peripheral blood involvement, and even spontaneous regression [2][3][4][5][6][7][8][9][10]. The average age of presentation is mid to late thirty with a female predominance (male: female=0.5) [2].…”
Section: Introductionmentioning
confidence: 99%